Preparation method and application of blended fabric composite material based on high-temperature-resistant fibers

CN119459099APending Publication Date: 2025-02-18SHANGHAI PRET COMPOSITES +1

Patent Information

Application Number
CN202411634743.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-18

Smart Images

  • Figure BDA0005136868060000111
    Figure BDA0005136868060000111
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a blended fabric composite material based on high-temperature-resistant fibers. After the carbon fibers and the liquid crystal polymer fibers are blended and woven, the woven fabric is overlapped and subjected to hot static pressure forming, then the mechanical property of the composite material is improved through a heat treatment process, and the obtained carbon fiber reinforced liquid crystal polymer composite material has the tensile strength larger than 200 MPa and can be used for large structural parts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a composition, in particular to a preparation method of a composite material based on a high-temperature resistant fiber blended cloth, belonging to the field of composite materials. Background Art

[0002] As an important cornerstone of the development of modern industry and high-tech, resin-based composite materials are one of the indispensable basic materials for national security and national economy. In recent years, with the vigorous development of my country's aerospace industry, advanced resin-based composite materials for space applications have developed rapidly, and there is a great demand for the preparation technology of high-performance, lightweight and large-size resin-based composite components.

[0003] Thermotropic liquid crystal polymer (LCP) is a high-performance polymer material, which is usually known for its high strength, high modulus, excellent melt processing properties, inherent flame retardancy, low water absorption, chemical corrosion resistance, good radiation resistance and high and low temperature impact resistance, as well as many uses at high temperatures. Therefore, it has a wide range of applications in aerospace, special industries, etc. However, for large components, the strength and toughness of pure LCP resin or chopped fiber reinforced LCP composite materials are still insufficient; and due to the fast crystallization speed of LCP materials, it is difficult to injection mold large components. Summary of the invention

[0004] The purpose of the present invention is to provide a high temperature resistant carbon fiber reinforced liquid crystal polymer composite material and a preparation method thereof, so as to solve the above technical problems.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] A preparation method of a high temperature resistant fiber blended cloth composite material, which is composed of a fiber cloth blended with carbon fiber and liquid crystal polymer fiber, and the preparation method is as follows:

[0007] (1) Carbon fibers and liquid crystal polymer fibers are blended into yarns, and the obtained blended yarns are introduced into a loom for weaving to obtain blended fabrics; the weight ratio of the carbon fibers used in the blended yarns is between 25% and 65%.

[0008] (2) The blended fabrics are stacked in layers in a mold cavity, and then pre-pressed into shape by a hot static pressing process. The hot static pressing process is carried out in an inert gas medium for 1-10 minutes, wherein the inert gas is at least one of nitrogen, argon and carbon dioxide, and the oxygen content is below 20 PPM. If the oxygen content is too high, the content of small molecules in the prepared liquid crystal polymer composite material will be too high, there will be gaps between the blended fabrics, and the tensile strength will be too low.

[0009] The processing temperature used in the hot static pressing process is in the range of the melting point of the liquid crystal polymer to a temperature 20° C. higher than the melting point of the liquid crystal polymer. The pressure used is 5-30 MPa.

[0010] (4) The blended fabric laminate after static pressing is heat treated to obtain a high temperature resistant carbon fiber reinforced liquid crystal polymer composite material.

[0011] In the above preparation method,

[0012] The carbon fiber refers to a high-strength and high-modulus fiber with a carbon content of more than 90%, selected from high-strength carbon fibers obtained by carbonizing polyacrylonitrile fibers, viscose-based fibers, and asphalt-based fibers as precursor fibers, and has a diameter between 5 and 15 microns.

[0013] The liquid crystal polymer is a liquid crystal polyester or polyester amide made using aromatic compounds as raw material monomers, and is preferably a fully aromatic liquid crystal polyester or polyester amide made using only aromatic compounds as raw material monomers.

[0014] A typical example of the liquid crystal polymer of the present invention is a liquid crystal polyester formed by polymerizing an aromatic hydroxycarboxylic acid and at least one compound selected from the group consisting of an aromatic hydroxylamine, an aromatic diamine, an aromatic dicarboxylic acid, and an aromatic diol. Part or all of the aromatic hydroxycarboxylic acid, aromatic hydroxylamine, aromatic diamine, aromatic dicarboxylic acid, and aromatic diol may be independently their polymerizable derivatives.

[0015] As the polymerizable derivative of a compound having a hydroxyl group such as an aromatic hydroxycarboxylic acid, an aromatic hydroxyamine, an aromatic diamine, or an aromatic diol, an acylated product formed by acylation of the hydroxyl group to convert it into an acyloxy group can be used.

[0016] In the combination of the above repeating units constituting the liquid crystal polymer:

[0017] The aromatic hydroxycarboxylic acid is selected from the repeating units of p-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid; the aromatic dicarboxylic acid is selected from the repeating units of terephthalic acid, isophthalic acid and 2,6-naphthalene dicarboxylic acid, preferably from the repeating units of terephthalic acid and isophthalic acid; the aromatic diol is selected from the repeating units of hydroquinone, 2,6-naphthalene diol and 4,4'-dihydroxybiphenyl, preferably from the repeating units of hydroquinone and 4,4'-dihydroxybiphenyl; the aromatic hydroxylamine is selected from the repeating units of p-aminophenol and p-aminonaphthol, preferably from the repeating units of p-aminophenol; the aromatic diamine is selected from the repeating units of p-phenylenediamine, 4,4'-biphenyl and 2,6-naphthalene diamine.

[0018] The liquid crystal polymer of the present invention contains at least one repeating unit of an aromatic hydroxycarboxylic acid.

[0019] In step (3), the laminate is placed in a vacuum or inert gas medium during the heat treatment, and the oxygen content is controlled to be below 20 ppm.

[0020] The heat treatment is carried out for 4-12 hours under an inert gas flow or vacuum condition, wherein the inert gas is at least one of nitrogen, argon and carbon dioxide, and the gas flow rate is greater than 10 mL / min; the vacuum condition is a vacuum degree less than or equal to 100 Pa, preferably less than 20 Pa. If the gas flow is too small or the vacuum degree is insufficient, the content of small molecules in the prepared liquid crystal polymer composite material will be too high and the tensile strength will be too low. The treatment temperature used in the heat treatment process is in the temperature range of 100°C below the melting point of the liquid crystal polymer to 20°C below the melting point of the liquid crystal polymer.

[0021] A liquid crystal polymer film dispersed with a toughening agent can be obtained by mixing the toughening agent with the liquid crystal polymer by a known blending method, so that the toughening agent is uniformly dispersed in the liquid crystal polymer. The obtained liquid crystal polymer dispersed with a toughening agent is subjected to a known extrusion film-forming method, blown film-forming or extrusion biaxial stretching film-forming to obtain a liquid crystal polymer film material dispersed with a toughening agent. The liquid crystal polymer film material dispersed with a toughening agent has a thickness between 20 and 200 microns.

[0022] The liquid crystal polymer is a thermotropic liquid crystal polymer having a melt viscosity of 20 to 50 Pa·s and a melting temperature of 260 to 350°C.

[0023] The present invention uses continuous fiber as a reinforcing phase, composites it with LCP fiber by blending, and then utilizes the solid phase polymerization property of LCP material to perform hot pressing to prepare a carbon fiber reinforced LCP composite material. The high temperature resistant fiber reinforced liquid crystal polymer composite material of the present invention is easy to prepare, has high strength, and can be used for large structural parts. DETAILED DESCRIPTION

[0024] The present invention is further described below by way of examples and comparative examples. Without violating the spirit of the present invention, the present invention should not be limited to the contents specifically shown in the following examples.

[0025] Product performance test method:

[0026] The present invention uses a differential scanning calorimeter (DSC 8000, PerkinElmer, USA) to test the melting point (T m), tested with reference to ASTM D3418 method. The present invention uses a capillary rheometer (RH 2200, Malvern, UK) to test the melt viscosity (MV), and tests with reference to ASTM D3835 method. The present invention uses a universal testing instrument to test the tensile strength and tensile modulus, and tests with reference to GBT 3354 method. The present invention uses a universal testing instrument to test the flexural strength and flexural modulus, and tests with reference to GB / T 3356 method. The present invention uses a heat deformation Vicat tester to test the heat deformation temperature, and tests with reference to GB / T1634 method. The present invention uses a pendulum impact tester to test the notched impact strength, and tests with reference to GB / T 1843 method.

[0027] Embodiment 1:

[0028] First, p-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid and acetic anhydride are reacted at a constant temperature of 120-130°C for 1 hour, then the temperature is raised to 185-195°C within 2 hours, and the temperature is further kept constant for 0.5-1 hour, and the acetylation reaction is completed; then the acetate obtained by the acetylation reaction is subjected to a melt polycondensation reaction, and the polymerization temperature is raised to a predetermined temperature within 3 hours to allow the polymerization reaction to proceed continuously; when the torque of the stirrer rises to a predetermined level, nitrogen is immediately introduced to terminate the polymerization reaction; the nitrogen pressure is increased to 2kg / cm 2 , release the liquid crystal polymer, name the obtained liquid crystal polymer LCP1 and measure the melting point and melt viscosity. The monomer ratio of the liquid crystal polymer is as follows: 73 mol% of p-hydroxybenzoic acid and 27 mol% of 6-hydroxy-2-naphthoic acid. Its melting point is about 280°C and its viscosity is about 35 Pa·s. LCP1 is hot-melt spun into LCP fiber with a fiber diameter of 50D, named LCP fiber 1.

[0029] 55 parts by weight of carbon fiber (SYT55S, Zhongfu Shenying Carbon Fiber Co., Ltd.) and 45 parts by weight of LCP fiber 1 are blended into yarn. The blended yarn has a diameter of about 50 microns. Both the warp and the weft use the blended yarn, and the carbon fiber / liquid crystal polymer fiber blended yarn fabric 1 is woven in a plain weave manner.

[0030] Fabric 1 is stacked in layers up to 10 layers in the mold cavity, and then the mold cavity is replaced with nitrogen, and then the mold cavity is sealed. Next, it is slowly heated to 285°C, and the hot static pressing process is carried out in a nitrogen medium for 3 minutes, and the oxygen content is controlled below 20PPM.

[0031] After that, the mold cavity temperature dropped to 250°C, and the heat treatment of the blended fabric laminate after static pressing process began. After the temperature dropped to 250°C, the nitrogen was exhausted and a vacuum was applied, with a vacuum degree of about 50Pa and an oxygen content controlled below 20ppm. The entire heat treatment process lasted for 8 hours, and finally a high temperature resistant carbon fiber reinforced liquid crystal polymer composite material was obtained, and its properties are shown in Table 1.

[0032] Embodiment 2:

[0033] First, p-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, hydroquinone and acetic anhydride are reacted at a constant temperature of 120-130° C. for 1 hour, then the temperature is raised to 185-195° C. within 2 hours, and the temperature is further raised to 0.5-1 hour, and the acetylation reaction is completed; then, the acetate obtained by the acetylation reaction is subjected to a melt polycondensation reaction with terephthalic acid, and the polymerization temperature is raised to a predetermined temperature within 3 hours to allow the polymerization reaction to proceed continuously; when the torque of the stirrer rises to a predetermined level, nitrogen is immediately introduced to terminate the polymerization reaction; and the nitrogen pressure is increased to 2 kg / cm 2 , release the liquid crystal polymer, name the obtained liquid crystal polymer LCP2 and measure the melting point and melt viscosity. The monomer ratio of the liquid crystal polymer is as follows: 42 mol% of p-hydroxybenzoic acid, 22 mol% of 6-hydroxy-2-naphthoic acid, 18 mol% of hydroquinone, and 18 mol% of terephthalic acid. Its melting point is about 340°C and its viscosity is about 42 Pa·s. LCP2 is hot-melt spun into LCP fiber with a fiber diameter of 50D, named LCP fiber 2.

[0034] 55 parts by weight of carbon fiber (SYT55S, Zhongfu Shenying Carbon Fiber Co., Ltd.) and 45 parts by weight of LCP fiber 2 are blended into yarn. The blended yarn has a diameter of about 50 microns. Both the warp and the weft use the blended yarn, and the carbon fiber / liquid crystal polymer fiber blended yarn fabric 2 is woven in a plain weave manner.

[0035] Fabric 2 is layered and stacked up to 10 layers in the mold cavity. Then the mold cavity is replaced with nitrogen and sealed. Then, the mold cavity is replaced with nitrogen and sealed. Then, it is slowly heated to 345°C and the hot static pressing process is carried out in a nitrogen medium for 3 minutes, and the oxygen content is controlled below 20PPM.

[0036] After that, the mold cavity temperature dropped to 260°C, and the heat treatment of the blended fabric laminate after static pressing process began. After the temperature dropped to 260°C, the nitrogen was exhausted and a vacuum was applied, with a vacuum degree of about 50Pa and an oxygen content controlled below 20ppm. The entire heat treatment process lasted for 8 hours, and finally a high temperature resistant carbon fiber reinforced liquid crystal polymer composite material was obtained, and its properties are shown in Table 1.

[0037] Embodiment 3:

[0038] First, p-hydroxybenzoic acid, 4-aminophenol, biphenol and acetic anhydride are reacted at a constant temperature of 120-130°C for 1 hour, then the temperature is raised to 185-195°C within 2 hours, and the temperature is further raised to 0.5-1 hour, and the acetylation reaction is completed; then, the acetamide ester obtained by the acetylation reaction is subjected to a melt polycondensation reaction with isophthalic acid, and the polymerization temperature is raised to a predetermined temperature within 3 hours to allow the polymerization reaction to proceed continuously; when the torque of the stirrer rises to a predetermined level, nitrogen is immediately introduced to terminate the polymerization reaction; and the nitrogen pressure is increased to 2kg / cm 2 , release the liquid crystal polymer, name the obtained liquid crystal polymer LCP3 and measure the melting point and melt viscosity. The monomer ratio of the liquid crystal polymer is as follows: 50 mol% of p-hydroxybenzoic acid, 8 mol% of 4-aminophenol, 21 mol% of biphenyl diphenol, and 21 mol% of isophthalic acid. Its melting point is about 370°C and its viscosity is about 41 Pa·s. LCP3 is hot-melt spun into LCP fiber with a fiber diameter of 50D, named LCP fiber 3.

[0039] 55 parts by weight of carbon fiber (SYT55S, Zhongfu Shenying Carbon Fiber Co., Ltd.) and 45 parts by weight of LCP fiber 3 are blended into yarn. The blended yarn has a diameter of about 50 microns. Both the warp and the weft use the blended yarn, and the carbon fiber / liquid crystal polymer fiber blended yarn fabric 3 is woven in a plain weave manner.

[0040] The fabric is stacked in 3 to 10 layers in the mold cavity, and then the mold cavity is replaced with nitrogen, and then the mold cavity is sealed. Next, it is slowly heated to 375°C and the hot static pressing process is carried out in a nitrogen medium for 3 minutes, and the oxygen content is controlled below 20PPM.

[0041] After that, the mold cavity temperature dropped to 260°C, and the blended fabric laminate after static pressing process was heat treated. After the temperature dropped to 260°C, nitrogen was continuously introduced and discharged from the other side of the mold cavity. The nitrogen flow rate was about 20mL / min, and the oxygen content was controlled below 20ppm. The whole heat treatment process lasted for 12 hours, and finally a high temperature resistant carbon fiber reinforced liquid crystal polymer composite material was obtained, and its properties are shown in Table 1.

[0042] Embodiment 4:

[0043] The fabric 3 is layered up to 10 layers in the mold cavity, and then the mold cavity is replaced with nitrogen, and then the mold cavity is sealed. Next, it is slowly heated to 375°C, and the hot static pressing process is carried out in a nitrogen medium for 3 minutes, and the oxygen content is controlled below 20PPM.

[0044] After that, the mold cavity temperature dropped to 260°C, and the heat treatment of the blended fabric laminate after static pressing process began. After the temperature dropped to 260°C, the nitrogen was exhausted and a vacuum was applied, with a vacuum degree of about 50Pa and an oxygen content controlled below 20ppm. The entire heat treatment process lasted for 8 hours, and finally a high temperature resistant carbon fiber reinforced liquid crystal polymer composite material was obtained, and its properties are shown in Table 1.

[0045] Embodiment 5:

[0046] The fabric 3 is layered up to 10 layers in the mold cavity, and then the mold cavity is replaced with nitrogen, and then the mold cavity is sealed. Next, it is slowly heated to 375°C, and the hot static pressing process is carried out in a nitrogen medium for 3 minutes, and the oxygen content is controlled below 20PPM.

[0047] After that, the mold cavity temperature dropped to 270°C, and the blended fabric laminate after static pressing process was heat treated. After the temperature dropped to 270°C, nitrogen was continuously introduced and discharged from the other side of the mold cavity. The nitrogen flow rate was about 100mL / min, and the oxygen content was controlled below 20ppm. The whole heat treatment process lasted for 5 hours, and finally a high temperature resistant carbon fiber reinforced liquid crystal polymer composite material was obtained, and its properties are shown in Table 1.

[0048] Embodiment 6:

[0049] The fabric 3 is layered up to 10 layers in the mold cavity, and then the mold cavity is replaced with nitrogen, and then the mold cavity is sealed. Next, it is slowly heated to 375°C, and the hot static pressing process is carried out in a nitrogen medium for 3 minutes, and the oxygen content is controlled below 20PPM.

[0050] After that, the mold cavity temperature dropped to 300°C, and the blended fabric laminate after static pressing process was heat treated. After the temperature dropped to 300°C, nitrogen was continuously introduced and discharged from the other side of the mold cavity. The nitrogen flow rate was about 20mL / min, and the oxygen content was controlled below 20ppm. The whole heat treatment process lasted for 4 hours, and finally a high temperature resistant carbon fiber reinforced liquid crystal polymer composite material was obtained, and its properties are shown in Table 1.

[0051] Embodiment 7:

[0052] The fabric is layered and stacked up to 10 layers in the mold cavity. The weight ratio of carbon fiber to LCP fiber 3 in the blended yarn is 25:75. Then the mold cavity is replaced with nitrogen, and then the mold cavity is sealed, and then slowly heated to 375℃. The hot static pressing process is carried out in a nitrogen medium for 3 minutes, and the oxygen content is controlled below 20PPM.

[0053] After that, the mold cavity temperature dropped to 260°C, and the blended fabric laminate after static pressing process was heat treated. After the temperature dropped to 260°C, nitrogen was continuously introduced and discharged from the other side of the mold cavity. The nitrogen flow rate was about 20mL / min, and the oxygen content was controlled below 20ppm. The whole heat treatment process lasted for 12 hours, and finally a high temperature resistant carbon fiber reinforced liquid crystal polymer composite material was obtained, and its properties are shown in Table 1.

[0054] Comparative Example 1:

[0055] The fabric 3 is stacked in 10 layers in the mold cavity, and then the mold cavity is replaced with nitrogen, and then the mold cavity is sealed. Then, it is slowly heated to 360°C, and the hot static pressing process is carried out in a nitrogen medium for 10 minutes, and the oxygen content is controlled below 20PPM.

[0056] After that, the mold cavity temperature dropped to 300°C, and the blended fabric laminate after static pressing process was heat treated. After the temperature dropped to 300°C, nitrogen was continuously introduced and discharged from the other side of the mold cavity. The nitrogen flow rate was about 20mL / min, and the oxygen content was controlled below 20ppm. The whole heat treatment process lasted for 8 hours, and finally a high temperature resistant carbon fiber reinforced liquid crystal polymer composite material was obtained, and its properties are shown in Table 1.

[0057] Comparative Example 2:

[0058] The fabric 3 is layered up to 10 layers in the mold cavity, and then the mold cavity is replaced with nitrogen, and then the mold cavity is sealed. Next, it is slowly heated to 375°C, and the hot static pressing process is carried out in a nitrogen medium for 30 minutes, and the oxygen content is controlled below 20PPM.

[0059] After that, the mold cavity temperature dropped to 270°C, and the blended fabric laminate after static pressing process was heat treated. After the temperature dropped to 270°C, nitrogen was continuously introduced and discharged from the other side of the mold cavity. The nitrogen flow rate was about 20mL / min, and the oxygen content was controlled below 20ppm. The whole heat treatment process lasted for 8 hours, and finally a high temperature resistant carbon fiber reinforced liquid crystal polymer composite material was obtained, and its properties are shown in Table 1.

[0060] Comparative Example 3:

[0061] The fabric 3 is layered up to 10 layers in the mold cavity, and then the mold cavity is replaced with nitrogen, and then the mold cavity is sealed. Next, it is slowly heated to 395°C, and the hot static pressing process is carried out in a nitrogen medium for 1 minute, and the oxygen content is controlled below 20PPM.

[0062] After that, the mold cavity temperature dropped to 260°C, and the blended fabric laminate after static pressing process was heat treated. After the temperature dropped to 260°C, nitrogen was continuously introduced and discharged from the other side of the mold cavity. The nitrogen flow rate was about 20mL / min, and the oxygen content was controlled below 20ppm. The whole heat treatment process lasted for 4 hours, and finally a high temperature resistant carbon fiber reinforced liquid crystal polymer composite material was obtained, and its properties are shown in Table 1.

[0063] Comparative Example 4:

[0064] The fabric 3 is layered up to 10 layers in the mold cavity, and then the mold cavity is replaced with nitrogen, and then the mold cavity is sealed. Next, it is slowly heated to 320°C, and the hot static pressing process is carried out in a nitrogen medium for 2 minutes, and the oxygen content is controlled below 20PPM.

[0065] After that, the mold cavity temperature dropped to 250°C, and the blended fabric laminate after static pressing process was heat treated. After the temperature dropped to 250°C, nitrogen was continuously introduced and discharged from the other side of the mold cavity. The nitrogen flow rate was about 20mL / min, and the oxygen content was controlled below 20ppm. The whole heat treatment process lasted for 4 hours, and finally a high temperature resistant carbon fiber reinforced liquid crystal polymer composite material was obtained, and its properties are shown in Table 1.

[0066] Comparative Example 5:

[0067] The fabric 3 is stacked in layers up to 10 layers in the mold cavity, and then the mold cavity is sealed and then slowly heated to 375° C., and the hot static pressing process is carried out in an air medium for 3 minutes.

[0068] After that, the mold cavity temperature dropped to 270°C, and the blended fabric laminate after static pressing process was heat treated. After the temperature dropped to 270°C, nitrogen was continuously introduced and discharged from the other side of the mold cavity. The nitrogen flow rate was about 20mL / min, and the oxygen content was controlled below 20ppm. The whole heat treatment process lasted for 8 hours, and finally a high temperature resistant carbon fiber reinforced liquid crystal polymer composite material was obtained, and its properties are shown in Table 1.

[0069] Comparative Example 6:

[0070] The fabric 3 is layered up to 10 layers in the mold cavity, and then the mold cavity is replaced with nitrogen, and then the mold cavity is sealed. Next, it is slowly heated to 375°C, and the hot static pressing process is carried out in a nitrogen medium for 3 minutes, and the oxygen content is controlled below 20PPM.

[0071] After that, the mold cavity temperature dropped to 270°C, and the heat treatment of the blended fabric laminate after static pressing process began. After the temperature dropped to 270°C, the nitrogen was exhausted and a vacuum was applied, with a vacuum degree of about 500Pa and an oxygen content of about 1000ppm. The entire heat treatment process lasted for 8 hours, and finally a high temperature resistant carbon fiber reinforced liquid crystal polymer composite material was obtained, and its properties are shown in Table 1.

[0072] Comparative Example 7:

[0073] The fabric 1 is stacked in layers up to 10 layers in the mold cavity, and then the mold cavity is replaced with nitrogen, and then the mold cavity is sealed. Next, it is slowly heated to 285°C, and the hot static pressing process is carried out in a nitrogen medium for 5 minutes, and the oxygen content is controlled below 20PPM.

[0074] After that, the mold cavity temperature dropped to 220°C, and the blended fabric laminate after static pressing process was heat treated. After the temperature dropped to 220°C, nitrogen was continuously introduced and discharged from the other side of the mold cavity. The nitrogen flow rate was about 20mL / min, and the oxygen content was controlled below 20ppm. The entire heat treatment process lasted for 24 hours, and finally a high temperature resistant carbon fiber reinforced liquid crystal polymer composite material was obtained, and its properties are shown in Table 1.

[0075] Comparative Example 8:

[0076] Fabric 2 is stacked in layers up to 10 layers in the mold cavity, and then the mold cavity is replaced with nitrogen, and then the mold cavity is sealed. Next, it is slowly heated to 345°C, and the hot static pressing process is carried out in a nitrogen medium for 5 minutes, and the oxygen content is controlled below 20PPM.

[0077] After that, the mold cavity temperature dropped to 300°C, and the blended fabric laminate after static pressing process was heat treated. After the temperature dropped to 300°C, nitrogen was continuously introduced and discharged from the other side of the mold cavity. The nitrogen flow rate was about 20mL / min, and the oxygen content was controlled below 20ppm. The whole heat treatment process lasted for 3 hours, and finally a high temperature resistant carbon fiber reinforced liquid crystal polymer composite material was obtained, and its properties are shown in Table 1.

[0078] Comparative Example 9:

[0079] The fabric 3 is layered up to 10 layers in the mold cavity, and then the mold cavity is replaced with nitrogen, and then the mold cavity is sealed. Next, it is slowly heated to 375°C, and the hot static pressing process is carried out in a nitrogen medium for 3 minutes, and the oxygen content is controlled below 20PPM.

[0080] After that, the mold cavity temperature dropped to 270°C, and the blended fabric laminate after static pressing process was heat treated. After the temperature dropped to 270°C, nitrogen was continuously introduced and discharged from the other side of the mold cavity. The nitrogen flow rate was about 2mL / min, and the oxygen content was controlled below 20ppm. The whole heat treatment process lasted for 12 hours, and finally a high temperature resistant carbon fiber reinforced liquid crystal polymer composite material was obtained, and its properties are shown in Table 1.

[0081] Comparative Example 10:

[0082] The fabric 3 is layered up to 10 layers in the mold cavity, and then the mold cavity is replaced with nitrogen, and then the mold cavity is sealed. Next, it is slowly heated to 375°C, and the hot static pressing process is carried out in a nitrogen medium for 3 minutes, and the oxygen content is controlled below 20PPM.

[0083] After that, the mold cavity temperature dropped to 270°C, and the blended fabric laminate after static pressing process was heat treated. After the temperature dropped to 270°C, nitrogen was continuously introduced and discharged from the other side of the mold cavity. The nitrogen flow rate was about 20mL / min, and the oxygen content was controlled below 20ppm. The whole heat treatment process lasted for 16 hours, and finally a high temperature resistant carbon fiber reinforced liquid crystal polymer composite material was obtained, and its properties are shown in Table 1.

[0084] Comparative Example 11:

[0085] The fabric 3 is layered up to 10 layers in the mold cavity, and then the mold cavity is replaced with nitrogen, and then the mold cavity is sealed. Next, it is slowly heated to 375°C, and the hot static pressing process is carried out in a nitrogen medium for 3 minutes, and the oxygen content is controlled below 20PPM.

[0086] After that, the mold cavity temperature dropped to 330°C, and the blended fabric laminate after static pressing process was heat treated. After the temperature dropped to 330°C, nitrogen was continuously introduced and discharged from the other side of the mold cavity. The nitrogen flow rate was about 20mL / min, and the oxygen content was controlled below 20ppm. The whole heat treatment process lasted for 4 hours, and finally a high temperature resistant carbon fiber reinforced liquid crystal polymer composite material was obtained, and its properties are shown in Table 1.

[0087] Comparative Example 12:

[0088] The fabric is layered and stacked up to 10 layers in the mold cavity, wherein the weight ratio of carbon fiber to LCP fiber 3 is 20:80. The mold cavity is then replaced with nitrogen, and then sealed, and then slowly heated to 375°C. The hot static pressing process is carried out in a nitrogen medium for 3 minutes, and the oxygen content is controlled below 20PPM.

[0089] After that, the mold cavity temperature dropped to 260°C, and the blended fabric laminate after static pressing process was heat treated. After the temperature dropped to 260°C, nitrogen was continuously introduced and discharged from the other side of the mold cavity. The nitrogen flow rate was about 20mL / min, and the oxygen content was controlled below 20ppm. The whole heat treatment process lasted for 12 hours, and finally a high temperature resistant carbon fiber reinforced liquid crystal polymer composite material was obtained, and its properties are shown in Table 1.

[0090] Comparative Example 13:

[0091] The fabric is layered and stacked up to 10 layers in the mold cavity, wherein the weight ratio of carbon fiber to LCP fiber 3 is 70:30. The mold cavity is then replaced with nitrogen, and then sealed, and then slowly heated to 375°C. The hot static pressing process is carried out in a nitrogen medium for 3 minutes, and the oxygen content is controlled below 20PPM.

[0092] After that, the mold cavity temperature dropped to 260°C, and the blended fabric laminate after static pressing process was heat treated. After the temperature dropped to 260°C, nitrogen was continuously introduced and discharged from the other side of the mold cavity. The nitrogen flow rate was about 20mL / min, and the oxygen content was controlled below 20ppm. The entire heat treatment process lasted for 12 hours, and the composite material finally obtained could not be formed.

[0093] Table 1 Summary of properties of liquid crystal polymer composite materials of Examples and Comparative Examples

[0094]

[0095] The properties of the high temperature resistant carbon fiber reinforced liquid crystal polymer composites prepared in Examples 1 to 7 and Comparative Examples 1 to 12 are shown in Table 1. During the hot static pressing process of the carbon fiber liquid crystal polymer fiber blended fabric, the liquid crystal polymer fiber is fully contacted and combined with the carbon fiber bundle, and itself is fused to form a composite material continuous phase matrix, and then subjected to high temperature heat treatment to increase the degree of polymerization of the liquid crystal polymer to reach the required molecular weight. Comparing Example 3 and Comparative Example 1, the temperature during the hot static pressing process is too low, which will cause the liquid crystal polymer to be weakly combined with the carbon fiber, and the matrix itself is not fully melted, resulting in poor overall strength of the obtained composite material. Comparing Example 3 and Comparative Examples 2 to 5, it can be seen that if the hot static pressing temperature is too high, the time is too long, or the oxygen content is too high, the mechanical properties of the obtained composite material will be poor, which is caused by the high temperature decomposition or oxidation of the liquid crystal polymer during this process. Comparing Example 3 and Comparative Examples 6 and 9, if the inert gas flow is too small or the vacuum is insufficient, the mechanical properties of the liquid crystal polymer composite material will not be significantly improved during the heat treatment process, and the strength requirements we need will not be met, and may even decrease. Comparing Example 3 with Comparative Examples 7-8, the heat treatment temperature is too low or the time is insufficient, and the performance of the composite material is basically not improved. Similarly, in Comparative Examples 10 and 11, if the heat treatment temperature is too high or the time is too long, the performance of the composite material cannot be improved, but is damaged. Comparing Example 3 with Comparative Example 12, the carbon fiber content is too low, which will make the overall strength of the obtained composite material fail to meet the required requirements.

[0096] The high temperature resistant fiber reinforced liquid crystal polymer composite material of the present invention is easy to prepare and has high strength, and can be used for large structural parts.

Claims

1. A method for preparing a composite material based on a high temperature resistant fiber blended fabric, characterized in that: The fiber cloth is composed of a blend of carbon fiber and liquid crystal polymer fiber, and the preparation method thereof is as follows: (1) blending carbon fiber and liquid crystal polymer fiber into yarn, introducing the obtained blended yarn into a loom for weaving treatment to obtain a blended fabric; the weight ratio of the carbon fiber used in the blended yarn is between 25% and 65%; (2) stacking the blended fabrics in layers in a mold cavity and then pre-pressing them into shape through a hot static pressing process; The hot static pressing process is carried out in an inert gas medium for 1-10 minutes, wherein the inert gas is at least one of nitrogen, argon and carbon dioxide, and the oxygen content is below 20 PPM; if the oxygen content is too high, the content of small molecules in the prepared liquid crystal polymer composite material will be too high, gaps will exist between the blended fabrics, and the tensile strength will be too low; The processing temperature used in the hot static pressing process is in the range of the melting point of the liquid crystal polymer to a temperature 20°C higher than the melting point of the liquid crystal polymer; the pressure used is 5-30MPa; (3) The blended fabric laminate after static pressing is heat treated to obtain a high temperature resistant carbon fiber reinforced liquid crystal polymer composite material.

2. A composite material based on high temperature resistant fiber blended fabric according to claim 1, characterized in that: The carbon fiber refers to a high-strength and high-modulus fiber with a carbon content of more than 90%, selected from high-strength carbon fibers obtained by carbonizing polyacrylonitrile fibers, viscose-based fibers, and asphalt-based fibers as precursor fibers, and has a diameter between 5 and 15 microns.

3. The composite material based on high temperature resistant fiber blended fabric according to claim 1, characterized in that: The liquid crystal polymer is a liquid crystal polyester or polyester amide made from aromatic compounds as raw material monomers.

4. The composite material based on high temperature resistant fiber blended fabric according to claim 1, characterized in that: The liquid crystal polymer is a liquid crystal polyester formed by polymerizing an aromatic hydroxycarboxylic acid and at least one compound selected from the group consisting of aromatic hydroxyamines, aromatic diamines, aromatic dicarboxylic acids and aromatic diols.

5. The composite material based on high temperature resistant fiber blended fabric according to claim 4, characterized in that: A part or all of the aromatic hydroxycarboxylic acid, aromatic hydroxyamine, aromatic diamine, aromatic dicarboxylic acid and aromatic diol may be independently polymerizable derivatives thereof.

6. The composite material based on high temperature resistant fiber blended fabric according to claim 4, characterized in that: In the combination of the repeating units constituting the liquid crystal polymer: The aromatic hydroxycarboxylic acid is selected from the repeating units of p-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid; the aromatic dicarboxylic acid is selected from the repeating units of terephthalic acid, isophthalic acid and 2,6-naphthalenedicarboxylic acid; the aromatic diol is selected from the repeating units of hydroquinone, 2,6-naphthalenediol and 4,4'-dihydroxybiphenyl; the aromatic hydroxylamine is selected from the repeating units of p-aminophenol and p-aminonaphthol; the aromatic diamine is selected from the repeating units of p-phenylenediamine, 4,4'-biphenyl and 2,6-naphthalenediamine.

7. The composite material based on high temperature resistant fiber blended fabric according to claim 4, characterized in that: The liquid crystal polymer of the present invention contains at least one repeating unit of an aromatic hydroxycarboxylic acid.

8. The composite material based on high temperature resistant fiber blended fabric according to claim 1, characterized in that: In step (3), the laminate is placed in a vacuum or inert gas medium during the heat treatment, and the oxygen content is controlled to be below 20 ppm; The heat treatment is carried out for 4-12 hours under an inert gas flow or vacuum condition, wherein the inert gas is at least one of nitrogen, argon and carbon dioxide, and the gas flow rate is greater than 10 mL / min; and the vacuum condition is a vacuum degree of less than or equal to 100 Pa; The treatment temperature used in the heat treatment process is in the temperature range of 100° C. below the melting point of the liquid crystal polymer to 20° C. below the melting point of the liquid crystal polymer.

9. A liquid crystal polymer film, characterized in that: The liquid crystal polymer film dispersed with a toughening agent can be prepared by mixing the toughening agent with the liquid crystal polymer by a known blending method so that the toughening agent is uniformly dispersed in the liquid crystal polymer; the obtained liquid crystal polymer dispersed with a toughening agent is formed by a known extrusion film forming method, blow molding or extrusion biaxial stretching film forming to obtain a liquid crystal polymer film material dispersed with a toughening agent.

10. The liquid crystal polymer film according to claim 9, characterized in that: The thickness of the liquid crystal polymer film material dispersed with toughening agent is between 20 and 200 microns.

11. The liquid crystal polymer film according to claim 9, characterized in that: The liquid crystal polymer is a thermotropic liquid crystal polymer having a melt viscosity of 20 to 50 Pa·s and a melting temperature of 260 to 350°C.

12. A molded product, characterized in that: The composite material is prepared by the preparation method described in any one of claims 1 to 8.

Citation Information

Patent Citations

  • Liquid crystal polymer woven fabric and preparation method

    CN111101256A

  • Preparation method of continuous fiber reinforced interlaminar shear liquid crystal polymer composite material

    CN118082242A

  • Preparation method of continuous fiber reinforced high-toughness liquid crystal polymer composite membrane material

    CN118185246A

  • Fabric comprised of fusible and infusible fibers, the former comprising a polymer which is capable of forming an anisotropic melt phase

    US4479999A

  • A strong, solid plastic-based composite material and a method for its manufacture

    WO1994029386A1

Cited By

  • Carbon fiber reinforced ultrahigh-temperature-resistant liquid crystal polymer composite material and preparation method thereof

    CN121136351A